In Silico Analysis And Develipment Of Antimalarial Compounds Against Dihydroorotate Dehydrogenase Using Chem-Bioinformatic Tools - RAMAZANI A; BORNA H (International Journal of Pharma and Bio Sciences, 2011)
Computational studies have been developed to unravel the mechanism of action of the anti-malarial drugs and to give guidelines for the development of new derivatives with improved efficiency. In this study, dihydroorotate dehydrogenase (DHOD) a key enzyme in de novo pyrimidine biosynthesis and the major source of electrons for the mitochondrial electron transport chain of intraerythrocytic malaria parasites was selected as a target for potential inhibitors. Beginning with the natural inhibitors found in crystallographed molecules representing *.pdb file, a general similarity search were done in PDB, NCI and PUBMED databases resemble probable antimalarial compounds. This made it possible to dock these ligand libraries with DHOD by FlexX 3.2, 2007 software and comparing the inter-molecular interactions and scores which are given to them by the software. The highest absolute value of interactions energies were considered be the best and proper ligands. These ligands were used for second 95% similarity search in PUBCHEM for proposed antimalarial compound which have the same mechanism as A26. As an interesting point among 400 found molecules was presence of quinolines. This could propose a new mechanism for these important anti-malarial agents.